식육추출가공품 중 갈비탕에서의 Staphylococcus aureus 성장예측모델 개발 - 손나리(Na-Ry Son); 김안나(An-Na Kim); 최원석(Won-Seok Choi); 윤상현(Sang-Hyun Yoon); 서수환(Soo-Hwan Suh); 주인선(In-Sun Joo); 김순한(Soon-Han Kim); 곽효선(Hyo-Sun Kwak); 조준일(Joon-Il Cho) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2017)
In this study, predictive mathematical models were developed to estimate the kinetics of Staphylococcus aureus growth in processed meat product galbitang. Processed meat product galbitang was inoculated with 0.1 mL of S. aureus culture and stored at 4, 10, 20, 37°C. The µmax (maximum specific growth rate) and LPD (lag phase duration) values were calculated. The primary model was used to develop a response surface secondary model. The growth parameters were analyzed using the square root model as a function of storage temperature. The developed model was confirmed by calculating RMSE (Root Mean Square Error) values as statistic parameters. The LPD decreased, but µmax increased with an increase in the storage temperature. At 4, 10, 20 and 37°C, R2 was 0.99, 0.98, 0.99 and 0.99, respectively; RMSE was 0.39. The developed predictive growth model can be used to predict the risk of S. aureus contamination in processed meat product galbitang; hence, it has potential as an input model for the risk assessment.